A Study on effect of formulation variable on durg relese pattern of extended release matrix tablet by using Plackett burman statistical design - AMARESH PRUSTY,; BIJON KUMAR GUPTA, (International Journal of Pharma and Bio Sciences, 2019)
The present topic involves development and optimization of extended-release (ER) tablets of Benidipine Hydrochloride (BH) by using a 3-factor at 2-level using Plackett-Burman (PB) statistical design. The study considered different independent factors at their low, high levels and studied drug release as per number of runs using design expert software. The present paper was focused on the usefulness of Plackett–Burman design in screening different factors for extending drug release in matrix tablets for an antihypertensive drug. Different factors are—Eudragit amount (X1), HPMC amount (X2), Chitosan amount (X3), Micro Crystalline Cellulose amount (X4) on the drug release pattern from the extended release matrix tablet. We have used Design Experiment 12-run statistical model software to know the most suitable factors which affect drug release and then analysis drug release property of formulation batches to know the drug release. The significance of the model was indicated by the ANOVA. Eudragitamount, HPMC amount had significant effect on the drug release.